Hybrid laser pointer detection algorithm based on template matching and fuzzy rule-based systems for domotic control in real home environments - Chávez, F.; Fernández, F.; Alcalá, R.; Alcalá-Fdez, J.; Olague, G.; Herrera, F. (Applied intelligence (Dordrecht, Netherlands), 2012)
A fundamental problem for disabled or elderly people is to manage their homes while carrying out an almost normal life, which implies using and interacting with a number of home devices. Recent studies in smart homes have proposed methods to use a laser pointer for interacting with home devices, which represents a more user-friendly and less expensive home device control environment. However, detecting the laser spot on the original non-filtered images, using standard and non-expensive cameras, and considering real home environments with varying conditions, is currently an open problem. This paper proposes a hybrid technique, where a classic technique used in image detection processes, such as Template Matching, has been combined with a Fuzzy Rule Based System for detecting a laser spot in real home environments. The idea is to use this new approach to improve the success rate of the previous algorithms used for detecting the laser spot, decreasing as much as possible the false offs of the system, because, the detection of a false laser spot could lead to dangerous situations. Using this new hybrid technique a better success rate has been obtained, eliminating almost completely the possibility of dangerous situations that may occur due to incorrect detection of the laser spot in real home environments.